Perceptions of virtual clinical learning in dentistry: Understanding student views on virtual dental clinics - Kiran Rehman; Omer Sheriff Sultan; Muneer Gohar Babar; Fareeza Marican; Syed Sarosh Mahdi (BMC Medical Education)
Abstract Background The Virtual Dental Clinics (VDCs) are designed in an interactive mode for undergraduate dental students to expose them to dental clinical cases in the form of didactic learning rather than experiential learning. VDCs simulate realistic dental practice scenarios within a virtual environment, providing students with opportunities to engage in clinical decision-making, patient interactions, and procedural simulations. Aim This study aims to assess students’ perceptions regarding the usefulness of Virtual Dental Clinics (VDCs) in simulated clinical training using a validated questionnaire. The study seeks to assess student perceptions on usefulness, satisfaction, ease of learning and ease of use of Virtual Dental Clinics as a clinical teaching and learning tool. Methodology The Virtual Dental Clinics were designed on themes from sub-specialities of dentistry. Themes for clinical case scenarios were selected and designed with the guidance of specialist faculty and the E-Learn department of International Medical University. “A total of 29 Year 3 dental students participated in the study after using the VDC for two weeks. Year 3 dental students were included, as they recently began clinical postings, lacking exposure to advanced clinical situations. A pre-piloted and validated questionnaire named the ‘USE questionnaire’ was utilized to assess student perceptions regarding the usefulness, ease of use, ease of learning, and satisfaction with VDCs.” Results Data analysis showed that students expressed significantly different opinions regarding the domains Usefulness & Ease of Learning (mean difference 0.48, p < 0.001) as well as Usefulness and Satisfaction (mean difference 0.43, p < 0.001). The significant results for the usefulness domains suggest that although the tool is effective in helping the user achieve their task, there is still room for improvement in making it more user-friendly and easier to learn as well as in overall user satisfaction. Our study evaluated the impact of Virtual Dental Clinics (VDCs) on student perceptions. Data analysis using Wilcoxon signed rank test with Bonferroni correction and found significant differences between ‘Uselessness’ and other domains, which demonstrated the perceived utility of VDCs as an educational tool in the clinical setting. Importantly, uselessness was rated significantly higher compared to ‘Ease of use (p < 0.001), ‘Ease of learning’ p < 0.001) and satisfaction (p < 0.001). No significant differences were observed between ‘Ease of use, ease of learning and satisfaction’ (p > 0.05). The results demonstrate VDCs efficacy in supporting educational needs of students. These findings suggest that while users perceived the tool as effective in task completion (usefulness), further improvements may be required to improve its ease of use, learnability, and overall satisfaction. The lack of significant differences among the latter three domains may indicate a comparable user experience in those aspects. Conclusion This study has provided an understanding of student perception across the various aspects of usefulness, satisfaction, ease of use, and ease of learning in virtual dental clinics. The significant differences between some domains highlight variability in end-user experience, providing rationale for future improvements and optimization of end-user experience.